Modular Establishment of a Diketopyrrolopyrrole‐Based Polymer Library via Pd‐Catalyzed Direct C–H (Hetero)arylation: a Highly Efficient Approach to Discover Low‐Bandgap Polymers. Issue 6 (31st January 2013) - Guo, Qiang; Dong, Jiaxing; Wan, Danyang; Wu, Di; You, Jingsong
Abstract A concise, highly efficient palladium‐catalyzed direct C–H (hetero)arylation is developed to modularly assemble a diketopyrrolopyrrole (DTDPP)‐based polymer library to screen low‐bandgap and near‐infrared (NIR) absorbing materials. The DTDPP‐based copolymers P1 and P2 with an alternating donor–acceptor–donor–acceptor (D–A–D–A) sequence and the homopolymer P9 exhibit planarity and excellent π‐conjugation, which lead to low bandgaps (down to 1.22 eV) as well as strong and broad NIR absorption bands (up to 1000 nm).